Evolution of the Autism-Associated Neuroligin-4 Gene Reveals Broad Erosion of Pseudoautosomal Regions in Rodents. (3rd February 2020) - Maxeiner, Stephan; Benseler, Fritz; Krasteva-Christ, Gabriela; Brose, Nils; Südhof, Thomas C
Abstract: Variants in genes encoding synaptic adhesion proteins of the neuroligin family, most notably neuroligin-4, are a significant cause of autism spectrum disorders in humans. Although human neuroligin-4 is encoded by two genes, NLGN4X and NLGN4Y, that are localized on the X-specific and male-specific regions of the two sex chromosomes, the chromosomal localization and full genomic sequence of the mouse Nlgn4 gene remain elusive. Here, we analyzed the neuroligin-4 genes of numerous rodent species by direct sequencing and bioinformatics, generated complete drafts of multiple rodent neuroligin-4 genes, and examined their evolution. Surprisingly, we find that the murine Nlgn4 gene is localized to the pseudoautosomal region (PAR) of the sex chromosomes, different from its human orthologs. We show that the sequence differences between various neuroligin-4 proteins are restricted to hotspots in which rodent neuroligin-4 proteins contain short repetitive sequence insertions compared with neuroligin-4 proteins from other species, whereas all other protein sequences are highly conserved. Evolutionarily, these sequence insertions initiate in the clade eumuroidea of the infraorder myomorpha and are additionally associated with dramatic changes in noncoding sequences and gene size. Importantly, these changes are not exclusively restricted to neuroligin-4 genes but reflect major evolutionary changes that substantially altered or even deleted genes from the PARs of both sex chromosomes. Our results show that despite the fact that the PAR in rodents and the neuroligin-4 genes within the rodent PAR underwent massive evolutionary changes, neuroligin-4 proteins maintained a highly conserved core structure, consistent with a substantial evolutionary pressure preserving its physiological function.